Online supercapacitor health monitoring using a balancing circuit. (August 2016) - Shili, Seïma; Hijazi, Alaa; Sari, Ali; Bevilacqua, Pascal; Venet, Pascal
Highlights: A novel online technique for the state of health monitoring of supercapacitors energy storage systems is proposed. The supercapacitor equivalent series resistance monitoring using balancing circuit already present at the terminal of the cell is presented. A test bench was realised in order to show the reliability of the new proposed approach. Abstract: In this paper, a novel online technique for the state of health monitoring of supercapacitors energy storage systems is presented. It is based on measuring the equivalent series resistance of the energy storage element representing its aging. The suggested approach uses a suitable balancing circuit connected to the terminal of the storage element in order to extract its actual parameters. This new method is characterized by its simplicity which makes it convenient for industrial applications. A test bench is developed in order to prove the new method's reliability and accuracy. Experimental results taken from the test bench and from an offline classical laboratory characterization method shows that the differences between both responses do not exceed 7%.